2019
DOI: 10.1007/s42380-019-00045-3
|View full text |Cite
|
Sign up to set email alerts
|

Intersections Between Multiple Forms of Bias-Based Bullying Among Lesbian, Gay, Bisexual, and Queer Youth

Abstract: Lesbian, gay, bisexual, and queer (LGBQ) youth experience more heterosexist bullying victimization than their straight peers, which contributes to mental health disparities. However, LGBQ youth may simultaneously experience other types of bias-based bullying (e.g., racist, cis-sexist, and able-ist bullying). Informed by intersectionality theory, this study describes intersections of LGBQ students' experiences of multiple forms of bias-based bullying and explores demographic correlates of individual types and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…In addition to the cultivation of empathy, respondents indicated that their parents' instrumental support around access to mental health care was especially important. TGE youth of color are likely to be exposed to multiple minority stressors, causing harm to youth mental health (Meyer, 2003; Shramko et al, 2019), and parents who interrupt this link by offering emotional support or by ensuring that their child can access mental health care providers (e.g., offering recommendations, setting up and managing appointments) are offering gender‐identity‐specific social support. Consistent with prior work (Jones et al, 2020), one participant mentioned the importance of culturally relevant mental health care, which ultimately helped the participant's parent become involved in supporting their child.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the cultivation of empathy, respondents indicated that their parents' instrumental support around access to mental health care was especially important. TGE youth of color are likely to be exposed to multiple minority stressors, causing harm to youth mental health (Meyer, 2003; Shramko et al, 2019), and parents who interrupt this link by offering emotional support or by ensuring that their child can access mental health care providers (e.g., offering recommendations, setting up and managing appointments) are offering gender‐identity‐specific social support. Consistent with prior work (Jones et al, 2020), one participant mentioned the importance of culturally relevant mental health care, which ultimately helped the participant's parent become involved in supporting their child.…”
Section: Discussionmentioning
confidence: 99%
“…For example, both heterosexual and LGBQ adolescents who live in states with antibullying laws listing sexual orientation specifically as a focus of the law have lower risk of reporting suicide attempts than adolescents who live in states whose antibullying statutes do not specify sexual orientation (Meyer et al, 2019). LGBTQ+-specific community resources have also been associated with other health outcomes among heterosexual youth, including consistent condom use (Eisenberg, 2002) and lower odds of bullying victimization (Shramko et al, n.d.). Identifying resources that positively affect the majority (i.e., heterosexual) population as well as the target (i.e., LGBTQ+) population may help build political will to expand these supports.…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…The 2018 School Experience Survey (LAUSD, n.d.a) showed that 8.3% of high school students and 5.6% of middle school students identified as "lesbian, gay, bisexual, transgender and/or queer." National data consistently cite that GSD students feel disproportionately unsafe at school (Berlan et al, 2010;Parent et al, 2020;Shramko et al, 2019). Yet, a surprising finding on LAUSD's (n.d.a) School Experience Survey was the slight differences in ratings of feeling safe at school between GSD and heterosexual students.…”
Section: Making Gsd Students Visiblementioning
confidence: 99%